Ranking of Urban Areas for the Comprehensive Assessment of Fire Damage - Oparin, Ivan D.; Iashin, Aleksandr A. (Economy of Regions, 2020)
One of the most important causes of partial or complete destruction of property is fire. Social and economic damage from fire substantially reduces the regional macroeconomic indicators. Thus, a complete and objective assessment of fire damage is a necessity. We hypothesise that a comprehensive assessment of fire damage significantly depends on the characteristics of areas and facilities, where the fire occurred. Such comprehensive assessment should necessarily include the ranking of urban areas and consider the characteristics of facilities located there. We noted that areas and facilities with heterogeneous functions are characterised by increased fire damage (partial or complete). We applied analytical research methods, as well as classification, typology and ranking methods. Based on a detailed analysis of domestic and foreign experience in the field of zoning and ranking of areas, we created a classification of facilities and areas for the comprehensive assessment of fire damage. As a result, we constructed a map of Ekaterinburg areas, taking into account the issues of the comprehensive assessment of fire damage. On the example of Ekaterinburg, we analysed atypical conjunctions of facilities and areas and proposed an index for adjusting complex fire damage. We suggested a simple and versatile approach to ranking areas that considers the heterogeneity of facilities and areas. Additionally, we analysed this phenomenon and its impact on the comprehensive assessment of fire damage. A promising direction for further research is the examination of the comprehensive assessment of fire damage in rural areas.